Assessment of patient safety culture among paramedical personnel at general and district hospitals, Fayoum Governorate, Egypt - Naglaa A. El-Sherbiny; Eman H. Ibrahim; Wafaa Y. Abdel-Wahed (SpringerOpen, 2020)
Abstract Background Healthcare is a high-risk industry that requires regular assessment of patient safety climate within healthcare organizations. This addresses the organizational cultural issues and explores the association between organizational climate and patient outcomes. This study aimed to assess patient safety culture among paramedical health employees at Fayoum general and district hospitals and to determine factors affecting their perception of patient safety. Methods A descriptive cross-sectional study was conducted at the general hospital and four district hospitals in Fayoum Governorate, Egypt, among 479 paramedical healthcare workers. The standardized Hospital Patient Safety scale (HSOPSC) that composed of 12 safety culture dimensions was used. Results The mean total safety score varies according to the participant's position and work area. The total patient safety score was 46.56%. No dimension reported score above 75%. The highest mean composite scores were for organizational learning and continuous improvement (65.36%) and teamwork within hospital units (63.09%). The lowest reported score was for communication openness (17.9%). More perception of safety dimensions was seen in females than males, participants in direct contact with patients, and those with work experience less than 10 years. Conclusion and recommendations Overall, the degree of patient safety is low at Fayoum public hospitals. No dimension scored above 75%, and 7 out of 12 dimensions scored less than 50%. Hence, continuous monitoring and updating of the ways of incident reporting is highly recommended. This may be done through setting up a web-based incident reporting system accessible for 24 h.